Biomechanical development and evaluation of a new framework for all-on-four rehabilitation - Vanessa Araujo SILVA; Allyson Henrique de Andrade FONSECA; Dimitri Ribas FONSECA; Paulo Isaías SERAIDARIAN (Universidade Estadual Paulista, 2019)
Abstract Introduction For complete rehabilitation of fully edentulous mandibles, the option for immediate loading determines the use of temporary prostheses that splint the installed implants. Although temporary prostheses with reinforcement provide rehabilitations with biomechanical benefits, the non-adoption of this recommendation coexists in different studies on immediate restorations. Objective This study evaluates a type of prosthesis to restore jaws by the all-on-four concept. Material and method: The mechanical behavior of prostheses with the modified framework was evaluated in vitro, under a cantilever mechanical unilateral bending test. Two representative groups were included in the all-on-four concept, with a G1 test group (n = 10) containing modified frameworks and a G2 control group (n = 10) that included full acrylic prostheses. The samples were submitted to thermal cycling with 500 cycles (5° ± 2 °C for 30 s, and 55° ± 2° for 30 s) and to the mechanical bending test on the cantilever. Result The Mann-Whitney test revealed a significant difference between G1 and G2 (p <0.001). In the descriptive evaluation, G1 averaged 830.50 N until the initial resin fracture, while the control group presented a mean of 403.58N. The maximum resistance until complete fracture was recorded in G1, with a mean of 903.03N, while in G2, a mean of 435.20N was recorded. The linear vertical component of the flexion was 0.68 mm and 0.39 mm until the initial fracture of the bar, respectively for G1 and G2. Conclusion The modified framework for the all-on-four protocol determined better mechanical performance when compared to the same full acrylic prosthesis model.